2014
DOI: 10.1002/jsc.1991
|View full text |Cite
|
Sign up to set email alerts
|

Brand Identity Process of Financial Cooperatives: An Austrian Case

Abstract: Financial institutions, be they cooperatives and operating through crowdfunding, have to pay attention to the identity they create and disseminate through their communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…They found that, for financing in both cases, good communication with the support of a valid and consistent identity is essential. In addition, the use of marketing tools for crowd funding is significant [74]. Corazzini et al (2015), Belleflamme et al (2015), and Cason and Zubrickas (2015) emphasized the effect of coordination of investors on attracting investment and campaign success [34,46,75].…”
Section: Figure 6 the Proposed Model For Entrepreneurs' Resistance Against Crowd Funding [65]mentioning
confidence: 99%
“…They found that, for financing in both cases, good communication with the support of a valid and consistent identity is essential. In addition, the use of marketing tools for crowd funding is significant [74]. Corazzini et al (2015), Belleflamme et al (2015), and Cason and Zubrickas (2015) emphasized the effect of coordination of investors on attracting investment and campaign success [34,46,75].…”
Section: Figure 6 the Proposed Model For Entrepreneurs' Resistance Against Crowd Funding [65]mentioning
confidence: 99%
“…These direct lending online platforms focus a lot on trust issues, moderated by relationship proximity and expertise of their stakehoders (Attuel‐Mendès, Caseau, & Bonescu, 2017). To build trust, they, therefore, need to be very careful in communicating their brand identity (Attuel‐Mendès, Caseau, & Bonescu, 2014) and need to manage relationships with their microfunders (Macht, 2014). They also experimented with adopting the practices of offline microfinance such as group lending to increase trust (Assadi & Ashta, 2014).…”
Section: Research Directionsmentioning
confidence: 99%
“…In contrast, it has been found that enhanced duration of the campaign leads to increased chances of success (Cordova et al , 2015; Ahlers et al , 2015). Another important point to consider regards selection of suitable brands, proper identification of entrepreneurs, and use of right tools and marketing to attract investment, which is the result of correct management in a campaign (Attuel-Mendès et al , 2014). As it is observed, there is no power of evaluation and monitoring in crowdfunding because of the asymmetry of information, inaccessibility of entrepreneurs and the presence of non-expert investors.…”
Section: Document Model Buildingmentioning
confidence: 99%